Social representations in the elderly and their influence on self-care - Marquez Terraza, Ana Victoria (Revista Cuidarte, 2022)
Introduction: Social representations are constructions that can determine the behaviors that older people carry out, including self-care behavior. Objective: This study is aimed to describe emergent representations of health, illness and quality of life and how these relate to self-care practices in a group of older people in the eastern region of the Mendoza province. Materials and Methods: A qualitative grounded theory study was conducted based on an emerging design with 30 people over 60 years old in the eastern region of the Mendoza province, who were not institutionalized patients and had not been diagnosed with a mental illness before. A non-probability voluntary response sample was used for selection and a semi-structured interview was applied as an instrument. Results: Older people were found to have a multidimensional social representation of health, illness causes and quality of life, including physical, psychological, social and cultural elements in their representations, which is in line with self-care strategies that older people consider important to carry them out. Discussions: Although the psychological dimension was given priority in health and illness social representation, the physical self-care strategies were excelled. Conclusions: Understanding the social representations of health, illness and older people’s quality of life can be a valuable tool when designing educational strategies and health and self-care promotion for such population. How to cite this article: Marquez−Terraza Ana Victoria. Representaciones sociales en las personas mayores y su influencia en el autocuidado. Revista Cuidarte. 2022;13(2): e2107. http://dx.doi.org/10.15649/cuidarte.2107